Quantifying the geographical distribution effect on decreasing aggregated nitrogen oxides intensity in the Chinese electrical generation system. (10th June 2019) - Wang, Junfeng; Qiu, Ye; Ma, Yupei; He, Shutong; Liu, Nan; Feng, Yinchang; Dong, Zhanfeng; Liu, Lingxuan
Abstract : Over the past 20 years, the spatial distribution of electrical generation and its relationship to cross-regional power transmission has impacted China's power generation system and significantly affected the total amount of NOx and the aggregated nitrogen oxides intensity (ANI) of the system. An investigation of the driving mechanisms of ANI that considers the unevenness of regional electricity generation will be crucial to future improvements in the NOx efficiency of the electrical generation system in China. In this study, we built a decomposition model for ANI by incorporating the spatial distribution of electrical generation and found that the spatial distribution of electricity generation together with energy-related factors gradually caused decreases in ANI. The efficiency of electricity generation presented the dominant inhibitory effect on ANI, but its effect size has weakened since 2010. In contrast, the fossil fuel structure of thermal power shows an increasingly positive effect on changes in ANI. The primary energy composition only slightly affected changes in ANI. Moreover, the changed geographical distribution of electricity generation is non-negligible and has a positive effect on reduction of the ANI of the Chinese electrical generation system. The transferred amount of local NOx emissions by cross-provincial electricity transmission, however, could cause lead to additional environmental costs for generators. This issue should receive more attention in the future. Highlights: The ANI of electrical generation has decreased by 33.18% over the past 20 years. Electrical generation efficiency inhibited ANI strongly but gradually weakened over time. The geographical distribution effect reduced the ANI but transferred environmental costs. The electrical generation structure will hopefully affect ANI reduction in future.